Results of Differential Treatment of Tenckhoff Catheter Exit Site/Tunnel Infection during Peritoneal Dialysis in Patients with End-Stage Chronic Kidney Disease - V.H. Mishalov (Počki, 2015)
Introduction. Tenckhoff catheter exit site infection (ESI) occurs in 0.05–1.05 cases per patient per year and is a risk factor of termination of peritoneal dialysis (PD). Objective of the work. To evaluate the efficacy of differentiated treatment for ESI in the three-year prospective comparative study. Materials and me-thods. We have examined and treated 141 patients receiving renal replacement therapy by PD. In comparison group (group C) (73 patients) treatment and prevention of ESI was carried out without a differentiated approach; in main group (group M) (68 patients) we have applied differentiated approach considering the category of ESI. Groups were representative by gender, age, concomitant pathology. Results. Within three years, ESI occurred in 67 (47.5 %) patients. In group M, three-year incidence of ESI was significantly lower — 26 (38.2 %) patients compared with that of in group C — 41 (56.2 %) patients (p = 0.033). In group M, cumulative incidence of ESI was lower during all three years of study. In the structure of ESI categories, which occurred for the first time, there were no significant differences between groups. The most common was equivocal ESI — 46.3 %, acute ESI — 43.3 %, cuff infection — 10.4 %. The cumulative incidence of catheter removal due to ESI was 17.8 % in group C and 5.9 % in group M (p = 0.026). The average time of catheter functioning during the study: in group M — 1,024.0 ± 13.1 days, in group C — 930.1 ± 32.2 days (p = 0.031). Conclusions. The use of preventive measures has reduced the three-year ESI incidence from 56.2 to 38.2 % (p = 0.033) and increased the average duration of PD without ESI from 729.8 ± 41.2 days to 854.9 ± 35.2 days (p = 0.023). The use of differential diagnostic and treatment approach to ESI reduces the rate of catheter removal due to ESI from 17.8 to 5.9 % (p = 0.026) and increases the average time of catheter functioning to 1,024.0 ± 13.1 days versus 930.1 ± 32.2 days (p = 0.031).